A study on technical cleanliness at automotive component assembly line - Nur Azaida Ruzlyn, Ruzini (2017)
This thesis deals with Technical Cleanliness based on VDA 19, which is implementation of Autonomous Maintenance (AM) and SS system. The project is done at a company producing electronic part for automotive industry in Malaysia. The objective of this thesis is to reduce the contaminated particles in assembly line by applying the AM and 5s system in production line. Major Cleaning, 5S and idea of designing and fabricate Particle Containers had been implement based on the AM concept. Besides, the project method to conduct SS is establish improvement and doing the Gemba Walk and observed the OFI (Opportunity for Improvement). The aim is to increase the cleanliness, tidiness and systematic to reduce the contaminated particle. For the result, these improvements that had been implemented shows that the Illig values reduce 70 percent.